The Portuguese in West Africa, 1415-1670 : a documentary history - Newitt, M. D. D. (Cambridge, U. K.: Cambridge University Press, 2010)
'The Portuguese in West Africa, 1415-1670 brings together a collection of documents - all in new English translation - that illustrate aspects of the encounters between the Portuguese and the peoples of North and West Africa in the period from 1400 to 1650. This period witnessed the diaspora of the Sephardic Jews, the emigration of Portuguese to West Africa and the islands, and the beginnings of the black diaspora associated with the slave trade. The documents show how the Portuguese tried to understand the societies with which they came into contact and to reconcile their experience with the myths and legends inherited from classical and medieval learning. They also show how Africans reacted to the coming of Europeans, adapting Christian ideas to local beliefs and making use of exotic imports and European technologies. The documents also describe the evolution of the black Portuguese communities in Guinea and the islands, as well as the slave trade and the way that it was organized, understood, and justified'--
Includes bibliographical references and index.
Keywords: Portuguese -- Africa, West -- History -- Sources; Slave trade -- Africa, West -- History -- Sources; Africa, West -- Discovery and exploration -- Portuguese -- Sources; Africa, West -- History -- To 1884 -- Sources